FATTY ACID PROFILE OF SHEEP AND HORSE MEAT UNDER AN EXTENSIVE PRODUCTION SYSTEM - Mamani-Linares, Lindon W. (2013)
This study compared the fat content and fatty acid profile of sheep and horse finished under grazing systems. The sheep (n=10) and horses (n=10) were slaughtered using Chilean standard procedures. Carcasses were stored for 24 h in a cold room (4 ºC). Analyses were carried out on the Longissimus lumborum muscle. Sheep meat had higher content of intramuscular fat and higher levels of saturated fatty acids, but lower levels of polyunsaturated fatty acids compared to horse meat (p<0.05). In the polyunsaturated to saturated fatty acid ratio and linoleic conjug content, sheep meat presented values lower than those founded for horse meat. However, sheep meat showed an n-6/n-3 (2.60) ratio within the recommended levels and good levels of desirable fatty acids (67.76%).